PERANCANGAN APLIKASI PENGAJUAN DAN PERSETUJUAN CUTI KARYAWAN DENGAN METODE ENGINE TWIGE BERBASIS WEB - zulkifli, ridwan; Anisah, Rr. Isni (STMIK Komputama Majenang, 2021)
The design of the application for the application and approval of employee leave is very useful to simplify and speed up the process of filing for leave to be applied at PT. XXX and can help improve performance in the HRD (Human Resource Development) Section because nowadays technology is growing rapidly with website-based applications. It is also hoped that the studies that have been carried out can inspire readers. By using xampp, the CodeIgniter Framework that we need in designing this application which also includes employee data, leave requests, leave approvals and reports on submissions and approvals for taking leave. In addition, in the design and development of this application there is an engine twige method to assist the performance of making application designs to make it look more attractive. Application settings are carried out by the admin both in the process of data security and data confidentiality. All of these things are used to accommodate the necessary data and streamline the application.